Analisis Pengelolaan Kinerja Organisasi Berbasis Balanced Scorecard Pada Kpp Madya Malang - Feri Ardana; Gatot Sudjono (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2020)
Purpose - The aims of this study are determine performance achievement and identify the constraints of implementation performance management based on Balanced Scorecard in KPP Madya Malang. Design/Methodology/Approach - This research combines qualitative and quantitative descriptive. The discussion is focused on discussing performance management based on the Balanced Scorecard which consists of four perspectives. Results and Discussion - The results showed that the Organizational Performance Value in Malang Malang KPP reached 101.74% meaning that overall the achievement of the Malang KPP Madya NKO had a good performance. Based on the description of the achievements of the NKO shows that the linkage of financial perspectives with non-financial perspectives has not created a maximum causal relationship. Conclusion – The results of study prove that the Organizational Perfomance at KPP Madya Malang in 2016 has a good performance and have the four Balanced Scoredcard perspectives is three perspectives are in green status such as customer perspective, internal business processes perspective, and growth and learning perspective, while the one perspective that shows red status is the Stakeholder perspective. Research Implications – It is expected that the results of this study can provide Feedback and Learning on the strategies that have been implemented and can develop strategic learning for continuous improvement and can also provide insight to the KPP Madya Malang about the importance of education in BSC-based performance management and rewards. Research Limitations – This study conducts performance appraisals only based on a Balanced Scorecard based measurement, further research can use measurement of more than one method to strengthen and assess the overall results.